2018
DOI: 10.1002/jper.18-0167
|View full text |Cite
|
Sign up to set email alerts
|

The salivary microbiome of diabetic and non‐diabetic adults with periodontal disease

Abstract: Although select microbiota increased in both diabetes and periodontal disease progression, these genera decreased in co-existing diabetes and periodontal disease. These findings suggest that the genera abundance continues to change with additional stress imposed by co-existing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 46 publications
(105 reference statements)
10
58
2
Order By: Relevance
“…All the disease groups displayed higher microbiota diversity (not conclusive for the T2DM group) and different patterns of microbial communities compared to the Health group, except for the Met group. Several previous reports also disclosed consistent results 17 , 22 , 29 . Generally speaking, the diversity and the relative abundance of oral bacteria increase in periodontitis patients with or without type-2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…All the disease groups displayed higher microbiota diversity (not conclusive for the T2DM group) and different patterns of microbial communities compared to the Health group, except for the Met group. Several previous reports also disclosed consistent results 17 , 22 , 29 . Generally speaking, the diversity and the relative abundance of oral bacteria increase in periodontitis patients with or without type-2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 82%
“…Due to the small sample size of the T2DM group, we found a recent paper that consists of patients with highly similar inclusion criteria with our T2DM and DAP group and has its sequencing data of saliva samples available to serve as a validation set to validate the reliability of the group data 22 . High quality reads with a sequencing depth of 30,000 was screened and a final validation set consisting of 16 T2DM patients and 15 DAP patients was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…This diversity difference remained in the young animals even after ligation, while the profiles in the adolescent animals began to approach 60% of the OTUs by 1 month postligation, similar to the maintenance of 60% to 70% of the OTUs during disease in the older animals. This type of finding has been reported for human periodontitis with lower diversity in disease samples, albeit findings vary (62)(63)(64)(65). It has also been reported that while members of the oral microbiome may differ across individuals, the functional genomics of the bacterial population are more similar in health, with substantial changes in the gene expression profiles of commensals with disease (9,20,66).…”
Section: Discussionsupporting
confidence: 60%
“…Several studies have compared SM in patients with diabetes to that of healthy controls by means of NGS, and in general, data show that diabetes associates with a decrease in bacterial diversity of SM [66][67][68]. In addition, higher salivary levels of P. gingivalis, T. forsythia and F. alocis were reported in patients with gestational diabetes [69], whereas only minor differences were identified in children with T2DM, when compared to obese and healthy controls, respectively [70].…”
Section: Diabetes and Obesitymentioning
confidence: 99%